Tumor associated macrophages in breast cancer progression: implications and clinical relevance - Stavrou, Maria; Constantinidou, Anastasia (Frontiers in Immunology, 2024)
Macrophages represent an immune cell population characterized by high plasticity and a range of properties and functions. Their activation status and specific phenotype are highly associated with their localization and the environmental cues they receive. The roles of macrophages in cancer development are diverse. Despite their antitumor effects at early stages of the disease, their presence in the tumor microenvironment (TME) has been linked to tumor promotion upon disease establishment. Tumor associated macrophages (TAMs) are key components of breast cancer TME and they have been associated with poor clinical outcomes.High TAM densities were found to correlate with tumor progression, increased metastatic potential and poor prognosis. Interestingly, considerably higher levels of TAMs were found in patients with triple negative breast cancer (TNBC)-the most aggressive type of breast cancercompared to other types. The present review summarizes recent findings regarding the distinct TAM subsets in the TME and TAM involvement in breast cancer progression and metastasis.It highlights the constant interplay between TAMs and breast cancer cells and its major contribution to the progression of the disease, including such aspects as, polarization of macrophages toward a tumor promoting phenotype, induction of epithelial to mesenchymal transition (EMT) in cancer cells and enhancement of cancer stem cell properties. Further, we discuss the clinical relevance of these findings, focusing on how a better delineation of TAM 2 involvement in breast cancer metastasis will facilitate the selection of more efficient treatment options.